The Effects of GnRH and hCG Used During and After Artificial Insemination on Blood Serum Progesterone Levels and Pregnancy Rate in Cows - Paksoy, Zahid; Kalkan, Cahit (Kafkas Univ, Veteriner Fakultesi Dergisi, 2010)
The aim of this study was to evaluate the effects of single and combined administrations of GnRH and hCG with and on the 12th day after artificial insemination (AI). Total 75 cows ranging from 2 to 3 years old were used as materials. All animals were divided into five groups randomly and inseminated in the first estrous period between days 40 and 80 after parturition. The first group received 10 mu g buserelin acetate both during AI and on the 12(th) day of AI. The second group was treated with 10 mu g buserelin acetate during AI and 1.500 IU hCG on the 12(th) day after AI. In the third group, 1.500 IU hCG was injected immediately and on the 12(th) day after AI. Cows in the fourth group was administered 1.500 IU hCG immediately and 10 mu g buserelin acetate on the 12(th) day after AI. The last group was left as control. The pregnancy was diagnosed with rectal examination between days 45 and 60 following AI. The proportion of cows diagnosed as pregnant was 40.0% (6/15) for group 1, 4 and 5, 46.7% (7/15) for group 2 and 3. As a result of current study, it is identified that GnRH and hCG administration during and at the 12(th) day after AI failed in increasing pregnancy rate and caused no statistically significant alteration in progesterone levels.
Keywords: Cow; Artificial insemination; GnRH; hCG; Pregnancy rates